Integrating Islam and science in curriculum and instruction: A case study at Al-Falah pesantren, Pamekasan - Sholihin Sholihin; Zainuddin Syarif; Nor Hasan; Rudy Haryanto (Universitas Papua, 2026)
This study examines how Islam–science integration is formulated and enacted in the curriculum and instructional practices of Al-Falah Pesantren, Pamekasan. This study employed a qualitative single-case study design. Data were collected through semi-structured interviews with 15 informants, five observations of classroom and academic activities, and analysis of institutional documents, from March to May 2026. The findings show that integration operates through connected educational layers: a tawhid-based epistemological vision, a hybrid curriculum, classroom and laboratory learning, Bahtsul Masail, digital leadership, and institutional support. Integration became most visible when classical Islamic texts, Qur’anic reflection, empirical observation, scientific reasoning, and ethical judgment were jointly used to address authentic issues such as environmental care, laboratory discipline, health, digital transactions, and social responsibility. However, the implementation remained uneven across subjects and educational levels, particularly in teacher collaboration, interdisciplinary planning, integrative assessment, and institutional evaluation. The study's conclusion is that the coexistence of religious and science subjects does not automatically result in substantive integration unless the institutional vision is translated into curriculum content, teaching strategies, learning activities, and assessable competencies.